2019
DOI: 10.1108/ajems-03-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of government expenditure on economic growth in Botswana

Abstract: Purpose The purpose of this paper is to examine the relationship between government expenditure and economic growth in Botswana over the period 1985‒2016. The study employed the auto-regressive distributed lag (ARDL) bounds testing approach in investigating the nexus. The study makes the argument that the effectiveness of public spending should be assessed not only against the amount of the expenditure but also by the type of the expenditure. The empirical findings showed that aggregate expenditure has a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
1
11
1
7
Order By: Relevance
“…Different results are shown by the government expenditure (GE) variable, which has a negative but not significant effect in the long run on Indonesia's national income in 2010-2019. This result is not in line with the research of Wu et al (2010), Musa & Jelilov (2016), Dudzevičiūtė et al (2017), Amusa & Oyinlola (2019) which found that government expenditure has a positive effect on economic growth in the long run. The influence of government spending on economic growth in this study has the same direction as the research results from Hasnul (2015) and Okoye et al (2019).…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Different results are shown by the government expenditure (GE) variable, which has a negative but not significant effect in the long run on Indonesia's national income in 2010-2019. This result is not in line with the research of Wu et al (2010), Musa & Jelilov (2016), Dudzevičiūtė et al (2017), Amusa & Oyinlola (2019) which found that government expenditure has a positive effect on economic growth in the long run. The influence of government spending on economic growth in this study has the same direction as the research results from Hasnul (2015) and Okoye et al (2019).…”
Section: Resultscontrasting
confidence: 75%
“…In the short-run, all independent variables influence economic growth. In short-term, household consumption and government expenditure have a positive effect on economic growth, which shows the same results as the research from Wang et al, 2016;Petkova, 2019;Alper, 2018;Sun & Deng (2013), but not in line with the research by Amusa & Oyinlola (2019) and Okoye et al (2019) which shows that in the short-run government expenditure has a negative effect to economic growth. Different results show by investment and net export variables, which negatively affect the short-run economic growth in Indonesia in 2010-2019.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…However, in the long term, the significant positive impact is experienced only in recurring spending. This proves that the effectiveness of government spending in the economy is dependent on resources and the effectiveness of public spending, which has to be assessed not only on its amount but also on the composition type (Amusa & Oyinlola, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, to maintain economic stability, state consistency is required to increase the amount of consumption, government spending, exports, and investment (Muazi & Arianti, 2013). For disaggregated government spending, Amusa & Oyinlola's (2019) observed that both routine and development spending have a significant, short-term positive impact on growth. However, in the long term, the significant positive impact is experienced only in recurring spending.…”
Section: Introductionmentioning
confidence: 99%